Washer the raccoon - Walsh, George Ethelbert, 1865-1941.; Prittie, Edwin John (Chicago : John C. Winston Company, 1922)
As a young raccoon, Washer is swept over Rocky Falls and is captured downstream by Sneaky the Wolf who takes him to his den. Luckily, Mother Wolf saves him from being eaten and raises him as one of her cubs.
Keywords: Raccoon -- Juvenile fiction; Animals -- Juvenile fiction